Imaging approach for determination of canopy structure in oil palm - Awal M. A. (Malaysian Society of Plant Physiology, 2019)
Leaf area index and the fractional interception photo-synthetically active radiation (PAR) (0.4? .7 µ) is two important factors of oil palm growth and development, which strongly control water, carbon and energy exchanges between vegetation and the atmosphere. They are used in many ecological model and simulation model, but difficult and time consume to measure directly in oil palm plantation. Hemispherical photography is a powerful tool, which was examined and evaluated in this study to estimation of leaf area index and fractional interception of PAR in oil palm. Photographs were taken from different ages palm (2, 3, 7, 9, 12 and 16 year olds). From each palm group 40 photograph were chosen for analysis and total 240 images were analysis in this study. Images were analysis by commercial software Hemi View 2.1 (Delta-T Devices, UK). The average LAI values found to be closer to real LAI values. For calculation of LAI value above 5 years, it was necessary to multiply by a corresponding conversion factor to find out true LAI from photography LAI. However, for less than 5 years palm (here 2 year and 3 year), photography LAI value was equal to true LAI value. A good linear relationship was found between gap fraction and leaf area index from the photographic results. The fractional interception of PAR was found slightly lower than quantum sensor values.